2016
DOI: 10.1158/1078-0432.ccr-15-2081
|View full text |Cite|
|
Sign up to set email alerts
|

A Promyelocytic Leukemia Protein–Thrombospondin-2 Axis and the Risk of Relapse in Neuroblastoma

Abstract: Purpose: Neuroblastoma is a childhood malignancy originating from the sympathetic nervous system with a complex biology, prone to metastasize and relapse. High-risk, metastatic cases are explained in part by amplification or mutation of oncogenes, such as MYCN and ALK, and loss of tumor suppressor genes in chromosome band 1p. However, it is fundamental to identify other pathways responsible for the large portion of neuroblastomas with no obvious molecular alterations.Experimental Design: Neuroblastoma cell lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The frequent deregulation of SCP1 and SCP3 in clear cell renal cell carcinoma and concomitant PML reduction results in mTOR-HIF1 axis activation, thus increasing tumor-associated angiogenesis and tumor burden in Xenograft models [ 153 ]. Alternatively, neuroblastoma contain low level of PML I and PML I-induced expression of thrombospondin-2 (TSP2), a potent angiogenic inhibitor [ 154 ]. Overexpression of PML I in aggressive neuroblastoma cancer cell lines restored inhibition of tumor-associated angiogenesis [ 154 ].…”
Section: Physiological and Pathological Role Of Pmlmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequent deregulation of SCP1 and SCP3 in clear cell renal cell carcinoma and concomitant PML reduction results in mTOR-HIF1 axis activation, thus increasing tumor-associated angiogenesis and tumor burden in Xenograft models [ 153 ]. Alternatively, neuroblastoma contain low level of PML I and PML I-induced expression of thrombospondin-2 (TSP2), a potent angiogenic inhibitor [ 154 ]. Overexpression of PML I in aggressive neuroblastoma cancer cell lines restored inhibition of tumor-associated angiogenesis [ 154 ].…”
Section: Physiological and Pathological Role Of Pmlmentioning
confidence: 99%
“…Alternatively, neuroblastoma contain low level of PML I and PML I-induced expression of thrombospondin-2 (TSP2), a potent angiogenic inhibitor [ 154 ]. Overexpression of PML I in aggressive neuroblastoma cancer cell lines restored inhibition of tumor-associated angiogenesis [ 154 ]. In addition to an intrinsic reduction of PML in cancer cells, it was shown that colorectal cancer cells are capable of reducing PML protein abundance in endothelial cells.…”
Section: Physiological and Pathological Role Of Pmlmentioning
confidence: 99%
“…amplification (Fig. 4a) [44]. For example, treatment with JVG045 at up to 20 μM in the MYCN-non-amplified cell line SHSY5 had no significant effect on cell number (One-way ANOVA, F (5,9) =1.157, p = 0.3989).…”
Section: Jvg045 Inhibits Kpc Mouse-derived Primary Cancer Cell Growthmentioning
confidence: 91%
“…These experiments showed that this compound is particularly active in inhibiting in vitro growth of human neuroblastoma cell lines containing an ampli cation of the MYCN proto-oncogene (Kelly, IMR32, LAN1), while having only a limited effect on neuroblastoma cell lines lacking MYCN ampli cation (Fig. 4A) (44). For example, treatment with JVG045 at up to 20mM in the MYCN-non-ampli ed cell line SHSY5 had no signi cant effect on cell number (One-way ANOVA, F (5,9) =1.157, p=0.3989).…”
Section: Re-nhc Complexes Show Anticancer Activity In Neuroblastoma Cmentioning
confidence: 94%